Adherence to 14-day radical cure for Plasmodium vivax malaria in Papua, Indonesia: a mixed-methods study - Rahmalia, A; Poespoprodjo, JR; Landuwulang, CUR; Ronse, M; Kenangalem, E; Burdam, FH; Thriemer, K; Devine, A; Price, RN; Peeters Grietens, K; Ley, B; Gryseels, C (BioMed Central, 2023)
Background: Reducing the risk of recurrent Plasmodium vivax malaria is critical for malaria control and elimination. Primaquine (PQ) is the only widely available drug against P. vivax dormant liver stages, but is recommended as a 14-day regimen, which can undermine adherence to a complete course of treatment. Methods: This is a mixed-methods study to assess socio-cultural factors influencing adherence to a 14-day PQ regimen in a 3-arm, treatment effectiveness trial in Papua, Indonesia. The qualitative strand, consisting of interviews and participant observation was triangulated with a quantitative strand in which trial participants were surveyed using a questionnaire. Results: Trial participants differentiated between two types of malaria: tersiana and tropika, equivalent to P. vivax and Plasmodium falciparum infection, respectively. The perceived severity of both types was similar with 44.0% (267/607) perceiving tersiana vs. 45.1% (274/607) perceiving tropika as more severe. There was no perceived differentiation whether malaria episodes were due to a new infection or relapse; and 71.3% (433/607) acknowledged the possibility of recurrence. Participants were familiar with malaria symptoms and delaying health facility visit by 1–2 days was perceived to increase the likelihood of a positive test. Prior to health facility visits, symptoms were treated with leftover drugs kept at home (40.4%; 245/607) or bought over the counter (17.0%; 103/607). Malaria was considered to be cured with ‘blue drugs’ (referring to dihydroartemisinin-piperaquine). Conversely, ‘brown drugs,’ referring to PQ, were not considered malaria medication and instead were perceived as supplements. Adherence to malaria treatment was 71.2% (131/184), in the supervised arm, 56.9% (91/160) in the unsupervised arm and 62.4% (164/263) in the control arm; p = 0.019. Adherence was 47.5% (47/99) among highland Papuans, 51.7% (76/147) among lowland Papuans, and 72.9% (263/361) among non-Papuans; p < 0.001. Conclusion: Adherence to malaria treatment was a socio-culturally embedded process during which patients (re-)evaluated the characteristics of the medicines in relation to the course of the illness, their past experiences with illness, and the perceived benefits of the treatment. Structural barriers that hinder the process of patient adherence are crucial to consider in the development and rollout of effective malaria treatment policies.